A microfluidic device for platelet aggregation assay. (September 2015) - Guo, Jianguang; Li, Xiaoyan; Cao, Yi; Yu, Ronghui; Wang, Qiong; Hu, Ning; Liu, Yang; Yang, Jun
In order to achieve a fast, high-efficiency analysis of platelet aggregation, a novel microfluidic chip was designed and fabricated based on the traditional measurement principle and method. The chip had a main channel and six branch channels, which were connected with their own inlets (outlets). The master of this chip was fabricated using the traditional photolithography methods. Polydimethylsiloxane chip was replica molded on the master. In the platelet aggregation assay, blood sample and coagulant were loaded from separate inlets on both sides of the chip. Due to the diffusion of analytes in the laminar flow, two analytes diffused and mixed with each other within the main channel and gradually aggregated. The distance from the mixing point to the aggregation point denoted the aggregation capacity of the blood sample. Compared with traditional measurement methods based on glass tubes, this microfluidic chip–based method is simple, highly efficient, rapid, low consuming, inexpensive, and has high repeatability. Furthermore, it may be made as a portable device for wide application in clinical analysis.